Effect of lithium-ion doping concentration on structural and optical properties of NiO films fabricated by magnetron sputtering. (March 2017) - Zhao, Yang; Wang, Hui; Gong, Xiaoyang; Wang, Jingge; Li, Hehe; Tang, Miaomiao; Li, Xinzhong
Abstract: In the present work, we report the dependence of lithium-ion (Li + ) doping concentration on structure, optical and electrical properties of NiO films fabricated by radio frequency (rf) magnetron sputtering. It was found that the NiO grains were increased with increase in lithium-ion concentration from an anomalous state to a cubic shape following the NaCl-type structure. The NiO films presented highly c-axis preferred orientation with significant (111) diffraction. The samples marked A-C under the lithium-ion concentration of 1 at.%, 3 at.%, and 5 at.% respectively have optical band gap values of 3.72 eV, 3.61 eV and 3.47 eV, respectively. Comparatively, the controllable electrical properties of NiO films can be achieved by the variations of crystal quality arise from the lithium-ion doping concentration. Highlights: NiO films were sputtered by magnetron sputtering at different Li + concentration. The Li + concentration is critical to effect the physical properties of the NiO films. The resistivities of NiO films decreased with increasing the Li + concentration.